Flowering and nutritional status of Gladiolus hybridus L. 'Black Velvet' following gibberellin treatment - Beata Janowska; Roman Andrzejak; Tomasz Kosiada; Monika Kwiatkowska; Dagmara Smolińska (Horticultural Science, 2018)
Flowering and nutritional status in Gladiolus hybridus L. 'Black Velvet' were assessed following gibberellic acid treatment (GA3). Treatment were applied to corm (12-14 diameter) by soaking for 30 min in water solutions of GA3 at 100, 350 and 600 mg/dm3 with a control consisting of soaking-in water. All GA3 treatments inhibited elongation of inflorescence shoots and stimulated spike elongation. None of the tested concentrations affected the number of developing flowers in the spike, except for the 100 mg/dm3 in the 2nd year of the study. All GA3 treatments stimulated calcium uptake, but had no effect on the uptake of other macronutrients. All the GA3 treatments increased manganese content in leavesbud did not affect copper content. GA3 at 600 mg/dm3 stimulated uptake of iron and boron at 600 mg/dm3 but inhibited both at lower concentrations. Zinc uptake was stimulated at 100 mg/dm3 but inhibited at higher concentration.